2021
DOI: 10.1111/all.15150
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome‐based identification of novel endotypes in adult atopic dermatitis

Abstract: The members of MAARS consortium group are listed in ACKNOWLEDGMENTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…For the identification of patient subgroups, we first compiled a set of genes with the highest variances in expression in baseline (m0) AD samples denoted as AD-specific hypervariable genes. 25 We selected genes that (1) showed a variance in expression of > _1 in the AD m0 samples, and (2) had a variance at least 2 times higher in the AD m0 samples compared to the healthy control samples. The Euclidean distance matrix was computed on the basis of those AD-specific hypervariable genes (n 5 34 genes) (using normalized (DESeq2 size factor normalization) and transformed (log 2 transformation counts), and agglomerative hierarchical clustering was performed using the ward.D2 linkage criteria.…”
Section: Discussionmentioning
confidence: 99%
“…For the identification of patient subgroups, we first compiled a set of genes with the highest variances in expression in baseline (m0) AD samples denoted as AD-specific hypervariable genes. 25 We selected genes that (1) showed a variance in expression of > _1 in the AD m0 samples, and (2) had a variance at least 2 times higher in the AD m0 samples compared to the healthy control samples. The Euclidean distance matrix was computed on the basis of those AD-specific hypervariable genes (n 5 34 genes) (using normalized (DESeq2 size factor normalization) and transformed (log 2 transformation counts), and agglomerative hierarchical clustering was performed using the ward.D2 linkage criteria.…”
Section: Discussionmentioning
confidence: 99%
“…This is of particular importance since interferon signaling represents a key feature of psoriatic inflammation. Previous studies demonstrated the interferon responses, especially IFITM1, IFITM2, and CCL5 were increased of in skin of patients with AD ( 41 , 42 ). In our study, we found a prioritized gene regulatory network of interferon signaling in psoriasis but not in AD, suggesting the interferon-mediated priming can contribute to the responses to different inflammatory factors in different conditions.…”
Section: Discussionmentioning
confidence: 89%
“…Th2 high and Th2 low endotypes have been hypothesized, supported by proteomic 116 and transcriptomic studies, 117…”
Section: Cla + T Cell Relationship With Ad Biomarkers and Targeted Th...mentioning
confidence: 89%